Correction: Statistical degradation modelling of Poly(D,L-lactide-co-glycolide) copolymers for bioscaffold applications. - Yaroslava Robles-Bykbaev; Javier Tarrío-Saavedra; Sara Quintana-Pita; Silvia Díaz-Prado; Francisco Javier García Sabán; Salvador Naya (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0204004.].